(untitled) (Medico Legal Update, 2020)
Objectives: To compare the effects of clonidine and moxonidine as add on therapy in patients of chronic kidney disease with hypertension. Method: It is an observational study of duration of one year. Patient who fall under the diagnostic criteria of chronic kidney disease with hypertension were selected randomly from those attending the routine medicine outpatient department and medicine wardat S.N. Medical College and associated hospital. Result and Conclusion: Study shows a slightly greater reduction in various parameters of chronic kidney disease like systolic BP, diastolic BP, pulse rate, blood urea, and serum creatinine with moxonidine group than clonidine group. But statistically there was no significant difference was found in both groups.